Folic acid modified Fe3O4 nanoclusters by a one-step ultrasonic technique for drug delivery and MR imaging. Issue 9 (31st January 2020) - Fei, Meng-Yu; Song, Meng-Meng; Wang, Pei; Pang, Gao-zong; Chen, Jing; Lu, Da-Peng; Liu, Rui; Zhang, Gui-Yang; Zhao, Ting-Ting; Shen, Yu-Xian; Yu, Yong-Qiang
Abstract : Water-soluble Fe3 O4 @F127@FA nanoclusters were prepared by a facile ultrasonic-treated method for MR imaging and targeted drug delivery. Abstract : Multifunctional nanoclusters based on Fe3 O4 nanoparticles for magnetic resonance imaging (MRI) and drug delivery are reported here. At first, oleic acid (OA)-coated Fe3 O4 nanoparticles were prepared. Then block copolymer Pluronic F127 or folic acid (FA) conjugated-Pluronic F127 was used to modify the hydrophobic nanoparticles to become hydrophilic Fe3 O4 @F127 nanoclusters via facile ultrasonic treatment. During this process, drug molecules can also be introduced into the nanoclusters and therefore the targeted drug delivery system was formed. Next, we verified the feasibility of the nanoclusters as drug delivery vehicles and magnetic contrast agents. The nanoclusters have an average size of 200 nm and remained stable in water for long periods. Folic acid-modified nanoclusters showed an enhanced intracellular uptake into HepG2 cells by using both cellular iron amount analysis and flow cytometry analysis. Besides, Fe3 O4 @F127@FA nanoclusters showed good compatibility in the tested concentration range and good sensitivity in T 2 -weighted MRI. The magnetic nanoclusters combined with drug delivery properties have greatly increased the significance in the diagnosis and therapy of diseases, which are suitable for systematical administration of hydrophobic drugs and simultaneously MRI diagnosis.